Classroom Interaction Analysis: Teacher Talk and Students’ Responses In Hospitality and Tourism Department of Grade x at SMK N 1 Solok Selatan - Hanny Dhea Fransisca; Yendra; Siska (Universitas Negeri Medan, 2024)
This study aims to identify the types of Teacher Talk used by the teacher and the corresponding student responses in the Hospitality and Tourism Department of grade X at SMK N 1 Solok Selatan. By understanding the types of Teacher Talk and student responses, this research is expected to provide useful insights to improve the effectiveness of the teaching and learning process in the classroom. This research is a Qualitative Descriptive study. The writer investigated two teachers and their students from class X Hospitality 1 and class X Hospitality 2, selected using total sampling techniques. An observation sheet was used as the research instrument. The results showed that English teacher (A) used indirect teacher talk, including accepting learner feelings, praising or encouraging learners, accepting or using learner ideas, and asking questions, as well as direct teacher talk, including lecturing, giving directions, and criticizing or justifying authorities. Meanwhile, English teacher (B) also used indirect teacher talk, including accepting or using learner ideas and asking questions, as well as direct teacher talk, including lecturing, giving directions, and criticizing or justifying authorities. Additionally, students responded with student talk responses and student talk initiation, and silence.Keywords: Teacher talk, Direct teacher talk, Indirect Teacher talk, Student responses